Promoting Tax Compliance In MSMEs: The Role of Taxpayer Awareness and Tax Sanctions - Mela Novita Rizki; Irma Siagian; Muammar Rinaldi (Outline Journal of Economic Studies, 2026)
Purpose: This study examines how taxpayer awareness and tax sanctions affect tax compliance among MSMEs in Medan City, addressing variability in compliance driven by internal knowledge and external enforcement. Methods: A quantitative explanatory design using multiple linear regression was applied. Data were gathered from MSMEs operating at least one year via validated questionnaires, supplemented by brief interviews and secondary sources. Independent variables include taxpayer awareness, perceived sanctions, tax knowledge, and business size (log omzet). Regression diagnostics (VIF, normality, heteroskedasticity) and robust standard errors ensured model validity. Results: Results indicate taxpayer awareness has the strongest positive and statistically significant effect on compliance. Perceived tax sanctions also positively influence compliance but with smaller magnitude. Tax knowledge and business size contribute significantly as well. The model explains about 56% of variance in compliance (R² ≈ 0.56). Diagnostic checks show no major violations that would undermine inference, though researchers are advised to monitor multicollinearity and condition number in future studies. Conclusions: Improving MSME tax compliance in Medan requires integrated strategies that combine practical tax education and simplified administration with proportional, consistent enforcement. Awareness-building appears most effective for sustainable compliance gains. Originality/value: The study provides recent empirical evidence from Medan MSMEs using a validated regression framework, highlighting the relative importance of awareness, sanctions, and knowledge in shaping compliance and offering actionable guidance for local tax authorities.